Approach to catheter ablation of left atrial flutters. (13th October 2019) - Markowitz, Steven M.; Thomas, George; Liu, Christopher F.; Cheung, Jim W.; Ip, James E.; Lerman, Bruce B.
Abstract: Left atrial tachycardias (ATs) most commonly occur after catheter or surgical ablation of atrial fibrillation and in patients with atrial myopathies. Pre‐existing scar in the left atrium (LA) can result in complex circuits, sometimes with narrow channels that can be detected with high‐resolution mapping. The most common forms of macroreentrant AT from the LA are variants of peri‐mitral and roof‐dependent reentry. Localized reentrant rhythms occur in the setting of fibrosis that gives rise to slow conduction and may occur adjacent to areas of prior ablation. The approach to treating these ATs involves first identifying the left atrial origin, defining the tachycardia circuit – which can be facilitated by ultrahigh density mapping and entrainment – and selecting a suitable isthmus to target for ablation. An important endpoint in ablating left atrial flutters is to establish and confirm bidirectional line of the block. Challenges in ablating these ATs include the presence of multiple tachycardias, defining circuits with complex activation patterns and achieving durable lines of block, particularly in the lateral mitral isthmus. Progress in treating these arrhythmias has come from new mapping technologies and the recognition of epicardial connections that allow for persistent conduction across ablation lesions. Also, advances in delivering energy to obtain complete transmural lesions promise to improve the long‐term success of ablating ATs from the LA.